THE USE OF CHEMICAL ADDITIVES FOR FISHERIES PRODUCT PRESERVATION - Mr Syamdidi (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2012)
Preservation  is  a  common  practice  in  processed  food products  including  fisheries  product.The purpose of preservation in food  is not only maintain the quality of  food but also to prolong theshelf  life  of  food  itself. Preservatives  can be  divided  into  two  groups  i.e.  natural  and chemicalpreservatives.  The  chemical  preservatives  potentially used  in  fishery  industry  are  nitrite,  sulfurdioxide,  benzoic acid  and,  sorbic  acid.  These  preservatives  have  their  own characteristics  oninhibition of microorganisms. Food characteristic such  as  pH, and aw are  the  key  factors on theactivity of antimicrobial agent.